PENGARUH MODEL PEMBELAJARAN JUCAMA BERBANTUAN APLIKASI MATH SOLVER TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS - Desvia Amanda Januarti; Astuti; Zulfah; Zulhendri; Molli Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the JUCAMA learning model assisted by the Math Solver application on students' mathematical critical thinking skills. The background of this research is the importance of developing critical thinking skills in mathematics learning, as well as the need to utilize learning models and technology that can support this process. This study uses a quantitative approach with a quasi-experimental design and involves seventh-grade students at MTs in Sawah Village as research subjects. Sample selection was done using purposive sampling with two classes: the experimental class using the JUCAMA model and the control class using expository learning. The research instruments include a critical thinking skills test covering indicators of interpretation, analysis, evaluation, and inference. The research results indicate that there is a significant influence of implementing the JUCAMA learning model assisted by the Math Solver application on improving students' critical thinking skills. Students who participated in learning using the JUCAMA model showed higher achievement in the indicators of interpretation, analysis, evaluation, and inference compared to students who underwent expository learning. These findings suggest that using the JUCAMA model with the support of digital technology can be an effective strategy in developing students' mathematical critical thinking skills.